2018
DOI: 10.2139/ssrn.3258815
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Using Short Video Through Group Work in Teaching Speaking to Indonesian English As Foreign Language (EFL) Students

Abstract: This research aims at finding out the efficacy of using short video in teaching speaking to Indonesian English as Foreign Language (EFL) students. The main question of this research: Is the use of short video through group work effective in teaching speaking to Indonesian EFL students? The significances of the research are (1) this study can be an addition in the persisting teaching speaking by using short video. (2) this study will also be helpful to curricular designers to integrate ICT for teaching and lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In addition, students’ collaborative attitude and self-efficacy during collaborative learning can enhance their interest in using IT ( Konak et al, 2019 ) and they will be more willing to use IT in collaborative and inquiry learning. In addition, with the rapid development of social media such as short videos, those teacher education students who have more teamwork were found in Masruddin’s (2018) study to explore through group collaboration and were more likely to adopt short videos to enhance their learning. Conversely, without a good sense of CS-E, they will not be motivated to learn, and it will be detrimental to the effectiveness of accepting and using short video learning with collaborative learning ( Zheng et al, 2020 ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, students’ collaborative attitude and self-efficacy during collaborative learning can enhance their interest in using IT ( Konak et al, 2019 ) and they will be more willing to use IT in collaborative and inquiry learning. In addition, with the rapid development of social media such as short videos, those teacher education students who have more teamwork were found in Masruddin’s (2018) study to explore through group collaboration and were more likely to adopt short videos to enhance their learning. Conversely, without a good sense of CS-E, they will not be motivated to learn, and it will be detrimental to the effectiveness of accepting and using short video learning with collaborative learning ( Zheng et al, 2020 ).…”
Section: Resultsmentioning
confidence: 93%
“…Studies have shown that short videos can promote pre-service students’ self-efficacy by sharing more video resources, which also makes them more likely to use short videos to complete learning tasks ( Liu et al, 2021 ). Teacher trainees, as a reserve of future teachers, should use information technology to facilitate collaborative learning and development of students ( Masruddin, 2018 ). Therefore, through the learning and application of short videos, we can not only increase teacher trainees’ learning engagement, but also promote their collaborative learning and inquiry behaviors ( Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…By means of explicit instruction and repeated exposure to the target vocabulary the receptive and the productive knowledge of vocabulary can be increased manifold. Recent studies (Masruddin, 2019;Pamintuan et al, 2018) showed beneficial aspects of adding Spell Bee game sessions and using networking applications like WeChat in improving students' vocabulary acquisition in foreign language. The researcher-created supplementary can be used for teaching the prescribed vocabulary in the target group under similar conditions with few such effective additions.…”
Section: Discussionmentioning
confidence: 99%
“…One group pre-test-post-test design has been useful in several studies on foreign language teaching making quantitative data visible for researchers (Prayoga, 2018;Masruddin, 2018;Sánchez, Hernández, Fernández, Díazm& Bastian, 2019;Senel, 2018;and Öztürk 2019).…”
Section: Groups Of Students From the Morning And The Afternoon Schedulesmentioning
confidence: 99%